The Influence of Transparency and Accountability in Village Fund Management in Ngablak District, Magelang Regency - Vega Yuliana; Susilaningtyas Budiana Kurniawati; Syahriar Abdullah (International Journal Business, Management and Innovation Review, 2025)
This study aims to examine the effect of transparency and accountability on village fund management in Ngablak District, Magelang Regency. The research employed an associative quantitative approach using primary data collected through questionnaires. The study involved seven villages as the population, with a total of 86 respondents selected as the sample. Data were analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that both transparency and accountability have a positive and significant effect on village fund management. These findings suggest that improving the openness of information and the responsibility of village apparatus can enhance the effectiveness and efficiency of fund allocation and utilization. However, this study is limited by the use of a survey method, which relies solely on the perceptions and responses of the participants. Therefore, future research is recommended to incorporate interviews or direct observation to provide a more comprehensive understanding of the dynamics involved in village fund management.